Implementasi Kontrol Proporsional Integral Derivative (PID) pada Robot Pengambil Gambar Untuk Keperluan Vlog - Fitra Sulung Syahriyar; Wahyu Setyo Pambudi (Universitas Budi Darma, 2021)
Video Blogs or Vlogs are a new way to present material interactively. During making videos, vloggers often find it challenging to carry out their activities in recording or taking videos themselves, so they need a camera operator. The presence of automation technology with a combination of computer vision can provide vloggers to produce work. The answer resulting from the variety of these two technologies is robot technology with a facial recognition system and can assist vlogger activities. Based on the test results, the automatic image-taking robot has face detection capabilities with a success rate of 80% for ten trials. This robot also can automatically maintain a distance from the vlogger, where the overall test results have a 90% success rate.